Investigation of thermo-mechanical behavior, proton transfer and methanol permeation of polymer electrolyte membrane in low sulfonated state modified with thermally stable surface functionalized graphene oxide nanosheets. (January 2021) - Ayaz, Sher; Yu, Hai-Yin
Abstract: Sulfonated polyether ether ketone is currently under investigation to replace the expensive Nafion® as polymer electrolyte membrane. Sulfonic acid group is hydrophilic in nature and plays a key role in proton transfer in polymer electrolyte membranes. The higher the degree of sulfonation the higher proton conductivity in sPEEK based polymer exchange membrane is achieved; however, high degree of sulfonation causes severe dimensional instability due to higher water uptake which in turn affects membrane fuel retention capabilities as well as thermo-mechanical strength. Graphene oxide nanosheets were functionalized with aryl dizonium salt of p-Aminobenzene sulfonic acid for modification of sPEEK in low sulfonated state (DS = 53%) to improve its proton conductivity and suppress fuel crossover. The functionalization was carried out to compensate for the possible dilution of proton exchangeable sites by fillers. The resulting membranes were characterized in terms of morphology, thermo-mechanical behavior, methanol permeability, water uptake, and proton conductivities. The results proved that sulfonated GO not only improved thermo-mechanical behavior of the membrane but also dramatically increased proton conductivity (47 mS cm −1 ) than pristine sPEEK (25 mS cm −1 ). The composite membranes showed highly reduced methanol crossover compared with pristine sPEEK. The electrochemical selectivity increased from 9.5 × 10 4 Scm −3 s (pristine sPEEK) to 26.9 × 10 4 Scm −3 s. Highlights: Thermally stable surface functionalized graphene oxide. SPEEK/SGO hybrid membrane with enhanced thermal and mechanical stability. Improved proton conductivity. Suppressed methanol permeability. Higher electrochemical selectivity.